Hay fever and asthma symptoms in conventional and organic farmers in The Netherlands. Issue 2 (3rd October 2006) - Smit, Lidwien A M; Zuurbier, Moniek; Doekes, Gert; Wouters, Inge M; Heederik, Dick; Douwes, Jeroen
Abstract : Background: Farming has been associated with respiratory symptoms and with protection against atopy. To date, effects of organic farming on respiratory health have not been studied. Aims: To (1) compare hay fever and asthma-like symptoms in organic and conventional farmers and (2) assess associations between current and childhood farm exposures and respiratory health effects by conducting a survey. Methods: Questionnaire data from 1205 conventional and 593 organic farmers were evaluated. Associations between health effects and farm exposures were assessed by logistic regression analyses. Results: Organic farmers reported less wheezing with shortness of breath and slightly more hay fever than conventional farmers. However, organic farming was not an independent determinant of hay fever when adjusted for farming practices and potential confounders. Livestock farmers who grew up on a farm had a threefold lower prevalence of hay fever than crop farmers without a farm childhood (odds ratio (OR) 0.3, 95% confidence interval (CI) 0.1 to 0.5). Both crop farmers who grew up on a farm and livestock farmers who did not grow up on a farm had a reduced prevalence, although less pronounced and not statistically significant. Use of disinfectants containing quaternary ammonium compounds was positively related to hay fever (OR 2.1, 95% CI 1 to 4.4). No effects of farming practices were found for asthma. Conclusions: Our study adds to the evidence that a farm childhood in combination with current livestock farming protects against allergic disorders. This effect was found for both organic and conventional farmers.